Sustainability conflicts in Coastal India : hazards, changing climate and development discourses in the Sundarbans - Ghosh, Aditya (Cham, Switzerland : Springer, 2018)
This multidisciplinary work analyses challenges to sustainable development amidst rapidly changing climate in the world?s largest delta? the Sundarbans. Empirical evidence unpacks grounded vulnerabilities and reveals their temporal socio-economic impacts. A novel concept of?everyday disasters? is proposed? supported by data and photographic evidence? that contests institutional disaster definition. Then it uncovers how the geopolitics of ecological governance and its hegemonic discourse dominate local policies, which in turn fail to address local socio-ecological concerns, adaptation needs and development aspirations. Absence of local vocabularies, cognitive values and socio-cultural contexts along with spatially constricted, exclusionary, top-down techno-science approaches further escalate knowledge-action gaps. Deconstruction of multiscalar conflicts between the global rhetoric and transformative postcolonial geographies offers an ethical, Southern perspective of sustainability.
Includes bibliographical references and index.
Online resource; title from PDF title page (SpringerLink, viewed December 8, 2017).
Keywords: Sustainable development -- Sundarbans (Bangladesh and India); Development studies; Sustainability; Human geography; Climate change; Regional geography; BUSINESS & ECONOMICS -- Industries -- General; Sustainable development; Asia -- Sundarbans; Electronic books